PROCESSES FOR PRODUCING FERMENTATION PRODUCTS USING FIBER-DEGRADING ENZYMES IN FERMENTATION - LAVIGNE, JAMES; MOXLEY, GEOFFREY; BORCH, KIM; LIU, JIYIN; FRICKMANN, JESPER; XU, HUI; JIN, QIMING; LIU, YE; TANG, LAN (2023)
Provided is a subject matter relates to a process for producing fermentation products from starch-containing material comprising the steps of: i) saccharifying using a carbohydrate-source generating enzyme; ii) fermenting using a fermenting organism; wherein at least one polypeptide having cellobiohydrolase activity, endoglucanase activity, or beta-glucosidase activity are present or added during fermentation or simultaneous saccharification and fermentation. The subject matter also relates to an enzyme blend or composition comprising the polypeptides. La présente invention concerne un procédé de production de produits de fermentation à partir d'un matériau contenant de l'amidon comprenant les étapes suivantes : i) saccharification en utilisant une enzyme générant une source de glucides ; ii) fermentation en utilisant un organisme de fermentation. Dans ce procédé, au moins un polypeptide ayant une activité cellobiohydrolase, une activité endoglucanase ou une activité bêta-glucosidase est présent ou ajouté pendant la fermentation ou la saccharification et la fermentation simultanées. L'invention concerne également un mélange d'enzymes ou une composition comprenant les polypeptides.